2014
DOI: 10.1186/1471-2431-14-1
|View full text |Cite
|
Sign up to set email alerts
|

The pot calling the kettle black: the extent and type of errors in a computerized immunization registry and by parent report

Abstract: BackgroundAccurate classification of children’s immunization status is essential for clinical care, administration and evaluation of immunization programs, and vaccine program research. Computerized immunization registries have been proposed as a valuable alternative to provider paper records or parent report, but there is a need to better understand the challenges associated with their use. This study assessed the accuracy of immunization status classification in an immunization registry as compared to parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
107
4

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 27 publications
7
107
4
Order By: Relevance
“…A growing number of clinical studies are being carried out with BMO supplements: the novel tool described here would be useful for tracking the metabolic fate of oligosaccharides in blood, urine, and stool, and would be of pivotal importance to validate the observed activities. 41,42 The ability to automate the database makes it an attractive tool for milk oligosaccharide research as it is not possible to predict the biological activity of oligosaccharides a priori without knowing their structural characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…A growing number of clinical studies are being carried out with BMO supplements: the novel tool described here would be useful for tracking the metabolic fate of oligosaccharides in blood, urine, and stool, and would be of pivotal importance to validate the observed activities. 41,42 The ability to automate the database makes it an attractive tool for milk oligosaccharide research as it is not possible to predict the biological activity of oligosaccharides a priori without knowing their structural characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…This may be so because children aged more than 6 months start crawling or walking which increases their exposure to infectious agents. Moreover, such children start complementary feeding, and this may increase their exposure to different types of infections through contaminated food and water [5, 10, 22, 2630]. …”
Section: Discussionmentioning
confidence: 99%
“…At that moment, being carrier of a genetic variant that potentially increases NO production (i.e., the A-allele) might be of critical relevance because NO is a key regulator intestinal blood flow, protector of the mucosa, and modulator of the inflammatory response101112. In addition, the infants homozygous for the C-allele might be more susceptible to NEC and arginine supplementation162021 might be particularly indicated in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that plasma arginine concentrations are even more decreased in preterm infants with NEC1416171819. Moreover, data from two small randomized controlled studies1620, pooled in a meta-analysis21, suggest that arginine supplementation reduces the incidence of NEC in preterm infants.…”
mentioning
confidence: 99%